Microwave and Optical Electric Field Interaction in Microwave Polarization Detector Based on Photonic Technology for EMC Measurement - Yusuf Nur Wijayanto; Hiroshi Murata; I Dewa Putu Hermida (National Research and Innovation Agency, 2016)
We analyze the interaction of microwave and optical electric field in a microwave polarization detector based on photonic technology for Electromagnetic Compatibility (EMC) measurement. The detector consists of two orthogonal optical waveguides and patch antennas embedded with two orthogonal gaps fabricated on an Electro-Optic (EO) crystal. Wireless microwave signals can be received, separated and converted directly to lightwave signals through optical modulation using the proposed detector. This detector operates with no external power supply and with low microwave distortion. Microwave polarization can be identified using the proposed interface. In addition, it enables us to measure the magnitude and phase of the wireless signal simultaneously. The analysis of the device was done and presented at the operation frequency of 26 GHz. The proposed interface can be applied for EMC measurement through the radio-over-fiber link.